Farnesol Emulsion as an Effective Broad-Spectrum Agent against ESKAPE Biofilms - Li Tan; Rong Ma; Adam J. Katz; Nicole Levi (MDPI AG, 2024)
The family of ESKAPE pathogens is comprised of Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter. Together they are the main contributors of nosocomial infections and are well established for their ability to "escape" antibiotics. Farnesol is an FDA-approved cosmetic and flavoring agent with significant anti-biofilm properties. In a proprietary emulsion, farnesol has been shown to be capable of disrupting S. aureus, P. aeruginosa, and A. baumannii biofilms. The current work demonstrates that this farnesol emulsion reduces the number of viable bacteria, while also leading to reductions in biomass, of the other three ESKAPE pathogens: Enterococcus faecium, Klebsiella pneumoniae, and Enterobacter, both in vitro and in an ex vivo human skin model. A concentration of 0.5 mg/mL was effective for impeding biofilm development of all three bacteria, while 1 mg/mL for E. faecium and K. pneumoniae, or 0.2 mg/mL for E. cloacae, was able to kill bacteria in established biofilms. Contrary to antibiotics, no resistance to farnesol was observed for E. faecium or K. pneumoniae. The results indicate that farnesol is effective for direct cell killing and also has the ability to induce biofilm detachment from surfaces, as confirmed using Live/Dead image analysis. Our findings confirm that farnesol emulsion is an effective broad-spectrum agent to impede ESKAPE biofilms.